Positively charged composite membrane as well as preparation method and application thereof

By introducing quaternary ammonium salt structure into the polyamide separation layer of the nanofiltration membrane and generating positively charged quaternary ammonium salt groups, the problem of poor retention of polyvalent metal cations by the existing nanofiltration membrane is solved, and the problem of insufficient retention of polyvalent metal cations is achieved. Efficient separation of magnesium lithium.

CN119425423AActive Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310975871.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14
Estimated Expiration
2043-08-03

AI Technical Summary

Technical Problem

The existing nanofiltration membrane has a low effect on multivalent metal cations such as Mg2+ or Ca2+, especially when groundwater contains a large number of these ions, it is difficult to achieve efficient removal.

Method used

By introducing a specific quaternary ammonium structure into the separation layer of the polyamide nanofiltration membrane, and the chemical reaction between the sulfonyl chloride group and the tertiary amine group is generated to generate positively charged quaternary ammonium groups, thereby improving the positive film Charge density and magnesium-lithium separation efficiency.

Benefits of technology

While maintaining high water flux, the retention effect of composite membrane on magnesium ions is significantly improved, and the efficiency of magnesium lithium separation is improved. It is suitable for the field of water treatment and separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425423A_ABST
    Figure CN119425423A_ABST
Patent Text Reader

Abstract

The invention relates to the field of membranes, and discloses a positively charged composite membrane as well as a preparation method and application thereof. The composite membrane comprises a bottom layer, a porous support layer and a polyamide separation layer which are arranged in sequence, wherein the polyamide separation layer comprises a quaternary ammonium salt structure as shown in a formula I and / or a formula II; in the imgabs0 #, X is halogen; and Ar1 and Ar2 are each independently a residue after a reaction of a monomer containing a sulfonyl chloride group. The polyamide separation layer of the positively charged composite membrane contains a specific quaternary ammonium salt structure, so that the positively charged composite membrane has a high magnesium-lithium separation coefficient while maintaining high water flux, and is particularly suitable for the field of water treatment separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the membrane field, and in particular to a positively charged composite membrane and a preparation method and application thereof. Background Art

[0002] Nanofiltration membrane is a pressure-driven membrane with a pore size between ultrafiltration and reverse osmosis, and the pore size is generally less than 1nm. Due to its advantages such as high retention rate for divalent salts and small organic molecules, good water permeability and low operating pressure, it is widely used in the fields of groundwater hardness removal, surface water organic matter removal and color, oil-water separation and organic solvent recovery.

[0003] At present, the separation layer of commercial nanofiltration membranes is made of polyamide material, which is formed by interfacial polymerization of polyamines and polyacyl chlorides. Since the residual acyl chloride groups on the membrane surface will hydrolyze into carboxyl groups, the surface of the polyamide membrane will be negatively charged. Due to the Donnan effect, polyamide nanofiltration membranes have excellent retention performance for divalent anions, such as sulfate; but for multivalent metal cations, such as Mg 2+ or Ca 2+ The interception effect is low. There is a large amount of Mg in the groundwater. 2+ With Ca 2+ If you want to achieve efficient removal, it is difficult to achieve with ordinary polyamide nanofiltration membranes. In order to improve the retention of multivalent metal cations by nanofiltration membranes, researchers often introduce positively charged groups, such as amino groups, quaternary ammonium salts, quaternary phosphonium salts, and guanidine groups, into the functional layer of nanofiltration membranes to improve the retention of multivalent metal ions by nanofiltration membranes through the Donan effect.

[0004] Positively charged nanofiltration membranes are not only used for groundwater de-hardening, but also have important applications in electroplating wastewater treatment and lithium extraction from salt lakes. Therefore, it is of great significance to develop positively charged nanofiltration membrane materials and preparation processes with industrial prospects. Summary of the invention

[0005] The purpose of the present invention is to overcome the disadvantage of low magnesium-lithium separation efficiency of nanofiltration membranes in the prior art, and to provide a positively charged composite membrane and a preparation method and application thereof. The polyamide separation layer of the positively charged composite membrane contains a specific quaternary ammonium salt structure, so that the positively charged composite membrane has a high magnesium-lithium separation coefficient while maintaining a high water flux, and is particularly suitable for the field of water treatment separation.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a positively charged composite membrane, wherein the composite membrane comprises a bottom layer, a porous support layer and a polyamide separation layer arranged in sequence;

[0007] Wherein, the polyamide separation layer contains a quaternary ammonium salt structure represented by Formula I and / or Formula II;

[0008]

[0009] Wherein, X is a halogen; Ar1 ​​and Ar2 are each independently a residue after the reaction of a monomer containing a sulfonyl chloride group.

[0010] A second aspect of the present invention provides a method for preparing a positively charged composite film, characterized in that the preparation method comprises the following steps:

[0011] S1, preparing a porous supporting layer on the bottom layer;

[0012] S2, the membrane layer obtained in step S1 is first contacted with an aqueous phase of a polyamine containing a tertiary amine group, and is second contacted with an organic phase containing a polyacyl chloride, and after heat treatment, a composite membrane containing a polyamide separation layer is obtained;

[0013] S3, contacting the composite membrane with an organic solution of a monomer containing a sulfonyl chloride group, and drying to obtain the positively charged composite membrane.

[0014] The third aspect of the present invention provides a positively charged composite membrane prepared by the above preparation method.

[0015] A fourth aspect of the present invention provides an application of the positively charged composite membrane in the field of water treatment and separation.

[0016] Through the above technical solution, the positively charged composite film provided by the present invention and its preparation method and application achieve the following beneficial effects:

[0017] The polyamide separation layer of the positively charged composite membrane provided by the present invention contains a specific quaternary ammonium salt structure, which significantly improves the positive charge density of the composite membrane, and utilizes the repulsive effect between positive charges to improve the interception effect of the composite membrane on magnesium ions, thereby improving the magnesium-lithium separation efficiency of the composite membrane while maintaining a high water flux of the composite membrane.

[0018] In the preparation method of the positively charged composite membrane provided by the present invention, a monomer containing a sulfonyl chloride group undergoes a biochemical reaction with a tertiary amine in a polyamide separation layer, and the tertiary amine is converted into a quaternary ammonium salt group with a positive charge. The repulsive effect between the positive charges improves the interception effect of the composite membrane on magnesium ions, thereby improving the magnesium-lithium separation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a schematic diagram of the reaction of benzenesulfonyl chloride with a tertiary amine on the surface of a polyamide separation layer in Example 1 of the present invention;

[0020] Figure 2a is the XPS spectrum of nitrogen atoms on the surface of the composite film of Example 1;

[0021] Figure 2b is the XPS spectrum of nitrogen atoms on the surface of the composite film of Comparative Example 1;

[0022] Figure 3 This is the XPS spectrum of sulfur atoms on the surface of the composite film of Example 1. DETAILED DESCRIPTION

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] The first aspect of the present invention provides a positively charged composite membrane, wherein the composite membrane comprises a bottom layer, a porous support layer and a polyamide separation layer arranged in sequence;

[0025] Wherein, the polyamide separation layer contains a quaternary ammonium salt structure represented by Formula I and / or Formula II;

[0026]

[0027] Wherein, X is a halogen; Ar1 ​​and Ar2 are each independently a residue after the reaction of a monomer containing a sulfonyl chloride group.

[0028] In the present invention, the polyamide separation layer of the positively charged composite membrane contains a specific quaternary ammonium salt structure, which significantly improves the positive charge density of the composite membrane. The repulsive effect between the positive charges is used to improve the interception effect of the composite membrane on magnesium ions, thereby improving the magnesium-lithium separation efficiency of the composite membrane while maintaining a high water flux of the composite membrane.

[0029] In the present invention, * refers to the bonding position where the quaternary ammonium salt structure is connected to the polyamide separation layer.

[0030] According to the present invention, X is Cl, Br or I.

[0031] According to the present invention, the monomer containing a sulfonyl chloride group is selected from benzenesulfonyl chloride, o-toluenesulfonyl chloride, m-toluenesulfonyl chloride, p-toluenesulfonyl chloride, 2-ethylbenzenesulfonyl chloride, 3-ethylbenzenesulfonyl chloride, 4-ethylbenzenesulfonyl chloride, 2-chlorobenzenesulfonyl chloride, 3-chlorobenzenesulfonyl chloride, 4-chlorobenzenesulfonyl chloride, 2-fluorobenzenesulfonyl chloride, 3-fluorobenzenesulfonyl chloride, 4-fluorobenzenesulfonyl chloride, 2-nitrobenzenesulfonyl chloride, 3-nitrobenzenesulfonyl chloride, 4-nitrobenzenesulfonyl chloride, 2-bromobenzenesulfonyl chloride, 3-bromobenzenesulfonyl chloride, 4- Bromobenzenesulfonyl chloride, 2-iodobenzenesulfonyl chloride, 3-iodobenzenesulfonyl chloride, 4-iodobenzenesulfonyl chloride, 4-chloro-3-nitrobenzenesulfonyl chloride, 2-chloro-4-fluorobenzenesulfonyl chloride, p-dodecylbenzenesulfonyl chloride, p-butylbenzenesulfonyl chloride, 5-chloro-2-methylbenzenesulfonyl chloride, 3,5-dichlorobenzenesulfonyl chloride, 4-isopropoxybenzenesulfonyl chloride, 4-(trifluoromethoxy)benzenesulfonyl chloride, p-acetamidobenzenesulfonyl chloride, 2-cyanobenzenesulfonyl chloride, 3-cyanobenzenesulfonyl chloride, 4-cyanobenzenesulfonyl chloride, 2,4,6-trimethylbenzenesulfonyl chloride Benzenesulfonyl chloride, 2,4,6-triisopropylbenzenesulfonyl chloride, 2,4,5-trichlorobenzenesulfonyl chloride, 2,5-dimethoxybenzenesulfonyl chloride, p-tert-butylbenzenesulfonyl chloride, 4-bromo-2-fluorobenzenesulfonyl chloride, 1-naphthalenesulfonyl chloride, 2-naphthalenesulfonyl chloride, 6-chloro-2-naphthalenesulfonyl chloride, 7-chloro-2-naphthalenesulfonyl chloride, 5-chloro-2-naphthalenesulfonyl chloride, 8-chloro-2-naphthalenesulfonyl chloride, 2-thiophenesulfonyl chloride, 2-chloropyridinesulfonyl chloride, 4,4'-oxybisbenzenesulfonyl chloride, 1,4-benzenedisulfonyl chloride, 1,3 At least one of -benzenedisulfonyl chloride, 4-amino-6-chloro-1,3-benzenedisulfonyl chloride, 1,2-benzenedisulfonyl chloride, 4,5-dichloro-1,3-benzenedisulfonyl chloride, 4,4'-biphenyledisulfonyl chloride, methylsulfonyl chloride, trichloromethylsulfonyl chloride, ethylsulfonyl chloride, 2-chloroethanesulfonyl chloride, propylsulfonyl chloride, butylsulfonyl chloride, 1,4-butanedisulfonyl chloride, 1,3-propanedisulfonyl chloride, 1,5-pentanedisulfonyl chloride, naphthalene-1,5-disulfonyl chloride and naphthalene-2,6-disulfonyl chloride.

[0032] Further, the monomer containing a sulfonyl chloride group is selected from at least one of benzenesulfonyl chloride, 1,4-benzenedisulfonyl chloride, 1,3-benzenedisulfonyl chloride, ethylsulfonyl chloride, 1,4-butanedisulfonyl chloride, 1,3-propanedisulfonyl chloride, 1,5-pentanedisulfonyl chloride and naphthalene-2,6-disulfonyl chloride.

[0033] According to the present invention, the content of nitrogen atoms in the quaternary ammonium salt structure in the positively charged composite film is 0.1-2 at.%; or the content of sulfur atoms in the positively charged composite film is 0.1-2 at.%

[0034] In the present invention, when at least one of the contents of nitrogen atoms or sulfur atoms in the quaternary ammonium salt structure of the positively charged composite membrane satisfies the above range, it indicates that the composite membrane surface has a high positive potential, so that the composite membrane has a significantly improved retention rate of multivalent metal cations.

[0035] Furthermore, the content of nitrogen atoms in the quaternary ammonium salt structure in the positively charged composite film is 0.5-1.5 at.%, or the content of sulfur atoms in the positively charged composite film is 0.5-1.5 at.%.

[0036] According to the present invention, the surface Zeta potential of the composite membrane is -10 mV to 5 mV.

[0037] In the present invention, when the surface Zeta potential of the composite membrane satisfies the above range, it indicates that the composite composite membrane has a high surface electrode potential. When it is used for lithium-magnesium separation, it can better repel divalent magnesium ions, making it difficult for magnesium ions in the liquid to pass through the composite membrane, while allowing monovalent lithium ions to pass as much as possible, thereby obtaining a higher magnesium-lithium separation efficiency.

[0038] Furthermore, the surface Zeta potential of the composite membrane is between -5mV and 5mV.

[0039] According to the present invention, the average pore size of the composite membrane is 0.1-0.4 nm.

[0040] In the present invention, when the average pore size of the composite membrane meets the above range, it indicates that the positively charged composite membrane has a high density. When it is used for lithium-magnesium separation, it can better exclude divalent magnesium ions, making it difficult for magnesium ions in the liquid to pass through the composite membrane, while allowing monovalent lithium ions to pass as much as possible, thereby obtaining a higher magnesium-lithium separation efficiency.

[0041] Furthermore, the average pore size of the composite membrane is 0.15-0.3 nm.

[0042] According to the present invention, the contact angle of the positively charged composite film is 40-70°.

[0043] In the present invention, when the contact angle of the positively charged composite membrane satisfies the above range, the surface of the positively charged composite membrane has excellent hydrophilicity, and when used for magnesium-lithium separation, the water flux of the composite membrane can be further improved.

[0044] Furthermore, the contact angle of the positively charged composite film is 40-60°.

[0045] In the present invention, the bottom layer and the porous support layer are not specifically limited, and can be made of various existing materials that have a certain strength and can be used for nanofiltration and reverse osmosis membranes.

[0046] In the present invention, the bottom layer is a non-woven fabric material, preferably polyester and / or polyethylene.

[0047] In the present invention, the porous support layer material may be at least one of polyethersulfone, polysulfone, polyarylether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone.

[0048] According to the present invention, the thickness of the bottom layer, the porous support layer, and the polyamide separation layer is not particularly limited, and can be a conventional choice in the art. However, in order to enable the three layers to play a better synergistic role, the obtained composite nanofiltration membrane can better have an excellent magnesium-lithium separation coefficient and a higher water flux. Preferably, the thickness of the bottom layer is 30-150 μm, preferably 50-120 μm; the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm; the thickness of the polyamide separation layer is 10-500 nm, preferably 50-300 nm.

[0049] A second aspect of the present invention provides a method for preparing a positively charged composite film, characterized in that the preparation method comprises the following steps:

[0050] S1, preparing a porous supporting layer on the bottom layer;

[0051] S2, the membrane layer obtained in step S1 is first contacted with an aqueous phase of a polyamine containing a tertiary amine group, and is second contacted with an organic phase containing a polyacyl chloride, and after heat treatment, a composite membrane containing a polyamide separation layer is obtained;

[0052] S3, contacting the composite membrane with an organic solution of a monomer containing a sulfonyl chloride group, and drying to obtain the positively charged composite membrane.

[0053] In the present invention, in the preparation method of the composite membrane, the monomer containing the sulfonyl chloride group is subjected to a biochemical reaction with the tertiary amine in the polyamide separation layer, and the tertiary amine is converted into a quaternary ammonium salt group with a positive charge. The repulsive effect between the positive charges improves the interception effect of the composite membrane on magnesium ions, thereby improving the magnesium-lithium separation efficiency.

[0054] In the present invention, there is no particular limitation on the method for preparing the porous supporting layer on the bottom layer. It can be prepared by conventional methods in the art, preferably by a phase inversion method. Specifically, a polymer solution of the porous supporting layer material is coated on one surface of the bottom layer, and the porous supporting layer is obtained by phase inversion.

[0055] In the present invention, the phase inversion method can preferably be: dissolving the supporting layer polymer material in a solvent to obtain a polymer solution with a concentration of 10-20 weight %, and degassing at 20-40°C for 10-180min; then coating the polymer solution on the bottom layer to obtain an initial membrane, and then soaking it in water at a temperature of 10-30°C for 10-60min to obtain the supporting layer polymer porous membrane through the phase inversion layer.

[0056] The solvent may be N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, or the like.

[0057] According to the present invention, in step S2, the polyamine containing a tertiary amine group is selected from at least one of polyethyleneimine, polyethylene polyamine, 1-aminopiperazine, 1,4-diaminopiperazine, 1,4-piperazine diethylamine and 1,4-bisaminopropylpiperazine. Preferably, the polyamine containing a tertiary amine group is selected from polyethyleneimine and / or polyethylene polyamine.

[0058] According to the present invention, the concentration of the polyamine containing tertiary amine groups in the aqueous phase of the polyamine containing tertiary amine groups is 0.1 wt%-10 wt%, preferably 0.5 wt%-2.5 wt%.

[0059] According to the present invention, the polyacyl chloride is selected from at least one of 1,3,5-benzenetricarboxylic acid chloride, 1,2-phthaloyl chloride, 1,3-phthaloyl chloride, 1,4-phthaloyl chloride and adipoyl chloride; preferably, the polyacyl chloride containing a tertiary amine group is selected from 1,3,5-benzenetricarboxylic acid chloride and / or 1,4-phthaloyl chloride.

[0060] According to the present invention, the concentration of the polyacyl chloride in the organic phase containing the polyacyl chloride is 0.01 wt%-1 wt%, preferably 0.1 wt%-0.5 wt%.

[0061] According to the present invention, the amounts of the aqueous phase of the polyamine containing tertiary amine groups and the organic phase containing polyacid chlorides are such that the mass ratio of the polyamine containing tertiary amine groups to the polyacid chlorides is 0.1-10:1.

[0062] In the present invention, when the mass ratio of the polyamine containing tertiary amine groups to the polyacyl chloride is controlled to meet the above range, it can ensure that the interfacial polymerization reaction between the polyamine containing tertiary amine groups and the polyacyl chloride is sufficient, thereby increasing the positive charge density on the surface of the obtained polyamide separation layer and improving the retention rate of divalent or higher metal salts.

[0063] Furthermore, the amounts of the aqueous phase of the polyamine containing tertiary amine groups and the organic phase containing polyacid chlorides are such that the mass ratio of the polyamine containing tertiary amine groups to the polyacid chlorides is 0.5-5:1.

[0064] In the present invention, there is no particular limitation on the type of solvent in the organic phase containing polyacid chlorides, as long as it can dissolve the polyacid chlorides. Preferably, the solvent of the organic phase is one or more of n-hexane, dodecane, n-heptane, and alkane solvent oil (Isopar E, Isopar G, Isopar H, Isopar L, and Isopar M).

[0065] According to the present invention, there is no special limitation on the interfacial polymerization conditions of the polyamine containing tertiary amine groups and the polyacid chlorides, and the interfacial polymerization can be carried out according to the conventional conditions in the art. However, in order to enable the three layers to play a better synergistic role and enable the obtained composite nanofiltration membrane to better have an excellent magnesium-lithium separation coefficient and a higher water flux, preferably, the first contact time is 5-100s, preferably 10-60s; the second contact time is 10-200s, preferably 20-120s; the heat treatment conditions include: the heat treatment temperature is 40-150°C, preferably 50-120°C; the heat treatment time is 0.5-10min, preferably 1-5min.

[0066] In the present invention, in step S2, the ratio of the volume of the aqueous phase of the polyamine containing tertiary amine groups to the membrane area of ​​the membrane layer obtained in step S1 is 0.05-1 mL / cm 2 , preferably 0.1-0.5 mL / cm 2 .

[0067] In the present invention, in step S2, the ratio of the volume of the organic phase containing polyacyl chloride to the membrane area of ​​the membrane layer obtained in step S1 is 0.01-0.5 mL / cm 2 , preferably 0.05-0.25mL / cm 2 .

[0068] According to the present invention, in step S3, the monomer containing a sulfonyl chloride group is selected from benzenesulfonyl chloride, o-toluenesulfonyl chloride, m-toluenesulfonyl chloride, p-toluenesulfonyl chloride, 2-ethylbenzenesulfonyl chloride, 3-ethylbenzenesulfonyl chloride, 4-ethylbenzenesulfonyl chloride, 2-chlorobenzenesulfonyl chloride, 3-chlorobenzenesulfonyl chloride, 4-chlorobenzenesulfonyl chloride, 2-fluorobenzenesulfonyl chloride, 3-fluorobenzenesulfonyl chloride, 4-fluorobenzenesulfonyl chloride, 2-nitrobenzenesulfonyl chloride, 3-nitrobenzenesulfonyl chloride, 4-nitrobenzenesulfonyl chloride, 2-bromobenzenesulfonyl chloride, 3-bromobenzenesulfonyl chloride, Chlorine, 4-bromobenzenesulfonyl chloride, 2-iodobenzenesulfonyl chloride, 3-iodobenzenesulfonyl chloride, 4-iodobenzenesulfonyl chloride, 4-chloro-3-nitrobenzenesulfonyl chloride, 2-chloro-4-fluorobenzenesulfonyl chloride, p-dodecylbenzenesulfonyl chloride, p-butylbenzenesulfonyl chloride, 5-chloro-2-methylbenzenesulfonyl chloride, 3,5-dichlorobenzenesulfonyl chloride, 4-isopropoxybenzenesulfonyl chloride, 4-(trifluoromethoxy)benzenesulfonyl chloride, p-acetamidobenzenesulfonyl chloride, 2-cyanobenzenesulfonyl chloride, 3-cyanobenzenesulfonyl chloride, 4-cyanobenzenesulfonyl chloride, 2,4,6- Trimethylbenzenesulfonyl chloride, 2,4,6-triisopropylbenzenesulfonyl chloride, 2,4,5-trichlorobenzenesulfonyl chloride, 2,5-dimethoxybenzenesulfonyl chloride, p-tert-butylbenzenesulfonyl chloride, 4-bromo-2-fluorobenzenesulfonyl chloride, 1-naphthalenesulfonyl chloride, 2-naphthalenesulfonyl chloride, 6-chloro-2-naphthalenesulfonyl chloride, 7-chloro-2-naphthalenesulfonyl chloride, 5-chloro-2-naphthalenesulfonyl chloride, 8-chloro-2-naphthalenesulfonyl chloride, 2-thiophenesulfonyl chloride, 2-chloropyridinesulfonyl chloride, 4,4'-oxybisbenzenesulfonyl chloride, 1,4-benzenedisulfonyl chloride, 1 ,3-benzenedisulfonyl chloride, 4-amino-6-chloro-1,3-benzenedisulfonyl chloride, 1,2-benzenedisulfonyl chloride, 4,5-dichloro-1,3-benzenedisulfonyl chloride, 4,4'-biphenyledisulfonyl chloride, methylsulfonyl chloride, trichloromethylsulfonyl chloride, ethylsulfonyl chloride, 2-chloroethanesulfonyl chloride, propylsulfonyl chloride, butylsulfonyl chloride, 1,4-butanedisulfonyl chloride, 1,3-propanedisulfonyl chloride, 1,5-pentanedisulfonyl chloride, naphthalene-1,5-disulfonyl chloride and naphthalene-2,6-disulfonyl chloride.

[0069] Further, the monomer containing a sulfonyl chloride group is selected from at least one of benzenesulfonyl chloride, 1,4-benzenedisulfonyl chloride, 1,3-benzenedisulfonyl chloride, ethylsulfonyl chloride, 1,4-butanedisulfonyl chloride, 1,3-propanedisulfonyl chloride, 1,5-pentanedisulfonyl chloride and naphthalene-2,6-disulfonyl chloride.

[0070] According to the present invention, in step S3, in the organic solution, the concentration of the monomer containing the sulfonyl chloride group is 0.01 wt%-5 wt%.

[0071] In the present invention, when the concentration of the monomer containing the sulfonyl chloride group in the organic solvent in step S3 is controlled to meet the above range, it can ensure that the monomer containing the sulfonyl chloride group can fully react with the tertiary amine group in the polyamide separation layer, thereby further improving the positive charge density on the surface of the obtained positively charged composite membrane and further reducing the average pore size of the positively charged composite membrane.

[0072] Furthermore, in step S3, in the organic solution, the concentration of the monomer containing the sulfonyl chloride group is 0.1 wt%-2.5 wt%.

[0073] In the present invention, there is no particular limitation on the type of solvent in the organic solution in step S3, and it may be, for example, n-hexane.

[0074] According to the present invention, the ratio of the volume of the organic solvent to the membrane area of ​​the composite membrane is 0.05-1 mL / cm 2 .

[0075] In the present invention, by controlling the volume of the organic solvent and the membrane area of ​​the composite membrane to meet the above range, it is possible to ensure that the surface of the composite membrane is in full contact with the monomer containing the sulfonyl chloride group, and to ensure that the monomer containing the sulfonyl chloride group can have a high reaction efficiency with the tertiary amine on the surface of the polyamide separation layer of the composite membrane, so that the surface of the positively charged composite membrane obtained finally contains more quaternary ammonium salt groups.

[0076] Furthermore, the ratio of the volume of the organic solvent to the membrane area of ​​the composite membrane is 0.1-0.25 mL / cm 2 .

[0077] According to the present invention, the contact conditions include: the contact time is 10s-10min, preferably 1min-5min.

[0078] In the present invention, there is no particular limitation on the contact temperature, and it may be, for example, room temperature (20-30° C.).

[0079] According to the present invention, the drying conditions include: drying temperature of 30-80°C, preferably 40-60°C; drying time of 0.5-5min, preferably 1-3min.

[0080] The third aspect of the present invention provides a positively charged composite membrane prepared by the above preparation method.

[0081] A fourth aspect of the present invention provides an application of the positively charged composite membrane in the field of water treatment and separation.

[0082] Other features and advantages of the present invention will be described in detail in the following detailed description.

[0083] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0084] In the following examples and comparative examples:

[0085] (1) The water flux of the composite membrane is tested by the following method: the composite membrane is placed in a membrane pool, the water permeation of the composite membrane is measured under the conditions of 0.5 MPa and a temperature of 25°C within a certain period of time, and the water flux is calculated by the following formula:

[0086] J = Q / (A·t), where J is the water flux, Q is the water permeability (L), and A is the effective membrane area of ​​the composite membrane (m 2 ), t is time (h).

[0087] (2) The desalination rate of the composite membrane was tested by the following method: the composite membrane was placed in a membrane pool, the original aqueous solution was 2000 ppm magnesium chloride or 2000 ppm lithium chloride, and after pre-pressing at 0.2 MPa for 0.5 h, the permeate was obtained at a pressure of 0.5 MPa, the concentrations of magnesium chloride and lithium chloride in the permeate were measured by ion chromatography, and the desalination rate was calculated by the following formula:

[0088] R=(C f -C p ) / C f ×100%, where R is the desalination rate, C f is the concentration of magnesium chloride or lithium chloride in the original solution (measured by conductivity meter), C p It is the concentration of magnesium chloride or lithium chloride in the permeate (measured by conductivity meter).

[0089] (3) The magnesium-lithium separation coefficient of the composite membrane was obtained by testing the following method: the composite membrane was placed in a membrane pool, the original aqueous solution was a mixture of 2000 ppm magnesium chloride and 100 ppm lithium chloride, and after pre-pressing at 0.2 MPa for 0.5 h, the permeate was obtained at a pressure of 0.5 MPa.

[0090] The magnesium-lithium separation coefficient is calculated by the following formula:

[0091] Where S is the magnesium-lithium separation coefficient, C Li,p and C Li,f are the concentrations of lithium ions in the permeate and raw material solution (measured by ion chromatography); C Mg,p and C Mg,f are the concentrations of magnesium ions in the permeate and raw solution (measured by ion chromatography), respectively.

[0092] (4) The nitrogen atom content in the quaternary ammonium salt structure in the positively charged composite film is measured by the following method:

[0093] Before measurement, the composite film was dried in an oven to constant weight, and the surface elemental composition of the composite film was determined using a SigmaProbe X-ray photoelectron spectrometer produced by Thermo VG, UK. The content of nitrogen atoms in the quaternary ammonium salt group in the composite film was calculated by the following formula:

[0094]

[0095] Among them, A N + Represents the peak area of ​​nitrogen atoms in the quaternary ammonium salt group in the XPS spectrum ( Figure 2a The peak area at the middle bond energy of 400-403 eV); A N represents the peak area of ​​nitrogen atoms in the separation layer in the XPS spectrum ( Figure 2a The sum of the peak areas at 396-403 eV in S N Represents the atomic content (at.%) of nitrogen atoms in the separation layer of the composite membrane.

[0096] (5) The sulfur atom content in the positively charged complex was directly measured using a Sigma Probe X-ray photoelectron spectrometer produced by Thermo VG, UK.

[0097] (6) Average pore size test of positively charged composite membrane: measured by PEG solute transfer method, the detailed steps are as follows:

[0098] (i) Testing the retention rate of composite membranes for PEG with different molecular sizes;

[0099] (ii) Linear fitting was performed between PEG size and retention rate in a logarithmic-probability coordinate system, and the PEG size corresponding to 50% retention rate was the average pore size of the separation membrane.

[0100] (7) Surface Zeta potential test of positively charged composite membrane: The test was carried out using a Surpass electrokinetic analyzer (Anton Paar), the circulating fluid was a dilute aqueous solution of KCl, and the pH of the test fluid was 7.

[0101] (8) Contact angle of positively charged composite film: The surface contact angle of the composite film sample was tested using the sessile drop method using a DSA100 surface contact angle meter produced by KRUSS, Germany. Before the test, the sample was dried in a 60°C vacuum oven for 30 min to remove surface and internal moisture. The dried film was then attached to a flat glass slide with double-sided tape. The volume of each water drop was 2 μL. The water drop was dropped on the film surface for 3 s and then tested immediately. The final contact angle was determined by taking the average value after multiple measurements.

[0102] (9) The thickness of each layer in the positively charged composite film was measured using a scanning electron microscope (SEM), model of which was Hitachi S-4800.

[0103] In addition, in the following examples and comparative examples:

[0104] Branched polyethyleneimine (weight-average molecular weight of 25000 g / mol), polyethylene polyamine, 1-aminopiperazine, 1,4-diaminopiperazine, 1,3,5-benzenetricarboxylic acid chloride, benzenesulfonyl chloride, 1,4-benzenedisulfonyl chloride, 1,3-benzenedisulfonyl chloride, ethylsulfonyl chloride, 1,4-butanedisulfonyl chloride, 1,3-propanedisulfonyl chloride, 1,5-pentanedisulfonyl chloride and naphthalene-2,6-disulfonyl chloride were all purchased from J&K Technology Co., Ltd., and other chemical reagents were purchased from Sinopharm Chemical Reagent Co., Ltd.

[0105] The support layer is prepared by a phase inversion method, and the specific steps are as follows:

[0106] A certain amount of polysulfone (number average molecular weight of 80000 g / mol) was dissolved in N,N-dimethylformamide to prepare a polysulfone solution with a concentration of 18 wt%, and degassed at 25°C for 120 min; then, the polysulfone solution was coated on a polyester non-woven fabric (with a thickness of 75 μm) using a scraper to obtain an initial membrane, which was then immersed in water at a temperature of 25°C for 60 min to allow the polysulfone layer on the surface of the polyester non-woven fabric to undergo phase transformation into a porous membrane, and finally washed with water three times to obtain a bottom layer-porous support layer with a total thickness of 115 μm.

[0107] Comparative Example 1

[0108] The above area is 400cm 2 The upper surface of the polysulfone support layer was contacted with 50 mL of an aqueous solution containing 0.5 wt% polyethyleneimine, and the solution was drained after contacting at 25°C for 60 seconds; then, the upper surface of the support layer was contacted with 25 mL of an Isopar E solution containing 0.1 wt% 1,3,5-benzenetricarboxylic acid chloride, and the solution was drained after contacting at 25°C for 60 seconds; then, the membrane was placed in an oven and heated at 70°C for 3 minutes to obtain a composite membrane D1. The mass ratio of polyethyleneimine to 1,3,5-benzenetricarboxylic acid chloride was 10:1.

[0109] Example 1

[0110] (1) The above area is 400cm 2The upper surface of the polysulfone support layer is contacted with 50 mL of an aqueous solution containing 0.5 wt% polyethyleneimine, and the liquid is drained after contacting at 25°C for 60 seconds; then, the upper surface of the support layer is contacted with 25 mL of an Isopar E solution containing 0.1 wt% 1,3,5-benzenetricarboxylic acid chloride, and the liquid is drained after contacting at 25°C for 60 seconds; then, the membrane is placed in an oven and heated at 70°C for 3 minutes to obtain a composite membrane. Among them, the mass ratio of polyethyleneimine to 1,3,5-benzenetricarboxylic acid chloride is 10:1.

[0111] (2) The obtained composite membrane was immersed in 200 mL of a n-hexane solution containing 0.5 wt % benzenesulfonyl chloride for 1 min, then taken out and dried at 50° C. for 1 min to obtain a positively charged composite membrane N1.

[0112] Figure 1 A schematic diagram of the reaction of benzenesulfonyl chloride with tertiary amine on the surface of the polyamide separation layer is given: benzenesulfonyl chloride reacts with the tertiary amine groups in the polyamide separation layer to generate positively charged quaternary ammonium salt groups.

[0113] Figure 2a and Figure 2b The XPS spectra of nitrogen atoms on the surface of the composite membranes of Example 1 and Comparative Example 1 are shown in FIG. Figure 2a and Figure 2b It can be seen that after the composite film was modified with benzenesulfonyl chloride, a new signal peak appeared at 401-402 eV, corresponding to the signal peak of the nitrogen atom in the quaternary ammonium salt group.

[0114] Figure 3 is the XPS spectrum of sulfur atoms on the surface of the composite film of Example 1, Figure 3 It can be seen that a signal peak corresponding to sulfur atoms appeared at 166-170 eV, confirming that benzenesulfonyl chloride was successfully modified onto the membrane surface.

[0115] Example 2

[0116] (1) The above area is 400cm 2 The upper surface of the polysulfone support layer is contacted with 50 mL of an aqueous solution containing 0.5 wt% polyethylene polyamine, and the solution is drained after contacting at 25°C for 60 seconds; then, the upper surface of the support layer is contacted with 25 mL of an Isopar E solution containing 0.1 wt% 1,3,5-benzenetricarboxylic acid chloride, and the solution is drained after contacting at 25°C for 60 seconds; then, the membrane is placed in an oven and heated at 70°C for 3 minutes to obtain a composite membrane. The mass ratio of polyethylene polyamine to 1,3,5-benzenetricarboxylic acid chloride is 10:1.

[0117] (2) The obtained composite membrane was immersed in 200 mL of a n-hexane solution containing 0.1 wt % benzenesulfonyl chloride for 1 min, then taken out and dried at 50° C. for 1 min to obtain a positively charged composite membrane N2.

[0118] Example 3

[0119] (1) The above area is 400cm 2 The upper surface of the polysulfone support layer is contacted with 50 mL of an aqueous solution containing 0.5 wt% of 1,4-diaminopiperazine, and the liquid is drained after contacting at 25°C for 60 seconds; then, the upper surface of the support layer is contacted with 25 mL of an Isopar E solution containing 0.1 wt% of 1,3,5-benzenetricarboxylic acid chloride, and the liquid is drained after contacting at 25°C for 60 seconds; then, the membrane is placed in an oven and heated at 70°C for 3 minutes to obtain a composite membrane. Among them, the mass ratio of 1,4-diaminopiperazine to 1,3,5-benzenetricarboxylic acid chloride is 10:1.

[0120] (2) The obtained composite membrane was immersed in 200 mL of a n-hexane solution containing 2.5 wt % benzenesulfonyl chloride for 1 min, then taken out and dried at 50° C. for 1 min to obtain a positively charged composite membrane N3.

[0121] Example 4

[0122] The preparation method is the same as that of Example 1, except that in step (2), 1,4-benzenedisulfonyl chloride is used instead of benzenesulfonyl chloride to prepare a positively charged composite membrane N4.

[0123] Example 5

[0124] The preparation method is the same as that of Example 1, except that in step (2), 1,3-benzenedisulfonyl chloride is used instead of benzenesulfonyl chloride to prepare a positively charged composite membrane N5.

[0125] Example 6

[0126] The preparation method is the same as that of Example 1, except that in step (2), ethylsulfonyl chloride is used instead of benzenesulfonyl chloride to prepare a positively charged composite membrane N6.

[0127] Example 7

[0128] The preparation method is the same as that of Example 1, except that in step (2), 1,4-butanedisulfonyl chloride is used instead of benzenesulfonyl chloride to prepare a positively charged composite membrane N7.

[0129] Example 8

[0130] The preparation method is the same as that of Example 1, except that in step (2), 1,5-pentanedisulfonyl chloride is used instead of benzenesulfonyl chloride to prepare a positively charged composite membrane N8.

[0131] Example 9

[0132] The preparation method is the same as that of Example 1, except that in step (2), naphthalene-2,6-disulfonyl chloride is used instead of benzenesulfonyl chloride to prepare a positively charged composite membrane N9.

[0133] Example 10

[0134] The preparation method is the same as that in Example 1, except that in step (2), benzenesulfonyl chloride and 1,4-benzenedisulfonyl chloride are used instead of benzenesulfonyl chloride, wherein the concentration of benzenesulfonyl chloride and 1,4-benzenedisulfonyl chloride is 0.25% by weight, respectively, to obtain a positively charged composite membrane N10.

[0135] Embodiment 11

[0136] The preparation method is the same as that of Example 1, except that in step (2), the concentration of benzenesulfonyl chloride is 0.01% by weight, and a positively charged composite membrane N11 is obtained.

[0137] Example 12

[0138] The preparation method is the same as that of Example 1, except that in step (2), the concentration of benzenesulfonyl chloride is 5% by weight, and a positively charged composite membrane N11 is obtained.

[0139] Example 13

[0140] The method of Example 1 was followed, except that in step (2), the concentration of benzenesulfonyl chloride was 7.5 wt %, to obtain a positively charged composite membrane N13.

[0141] Embodiment 14

[0142] The method of Example 1 was followed, except that in step (2), the concentration of benzenesulfonyl chloride was 0.001 wt %, to obtain a positively charged composite membrane N14.

[0143] Comparative Example 2

[0144] The method of Example 1 was followed, except that in step (1), 1,4-cyclohexanediamine was used instead of polyethyleneimine to obtain a composite membrane D2.

[0145] The thickness of each layer of the composite membrane in the embodiments and comparative examples, the surface Zeta potential, the average pore size, the content of nitrogen atoms in the quaternary ammonium salt structure in the positively charged composite membrane, the content of sulfur atoms in the positively charged composite membrane, and the contact angle are shown in Table 1.

[0146] Table 1

[0147]

[0148] a It refers to the content of nitrogen atoms in the quaternary ammonium salt structure in the positively charged composite membrane.

[0149] bIt refers to the content of sulfur atoms in the positively charged composite film.

[0150] It can be seen from Table 1 that when the composite membrane is contacted with the monomer containing the sulfonyl chloride group, the tertiary amine in the polyamide separation layer reacts chemically with the sulfonyl chloride group, so that the tertiary amine is converted into a quaternary ammonium salt group with a positive charge, thereby increasing the positive charge density on the surface of the prepared positively charged composite membrane and increasing the hydrophilicity. In addition, after the polyamide separation layer is modified with the sulfonyl chloride group, the average pore size of the nanofiltration membrane separation layer is reduced, indicating that after the sulfonyl chloride monomer is modified into the polyamide separation layer, the free volume between the molecules is reduced.

[0151] It can be seen from Comparative Example 2 that only when the polyamide separation layer contains tertiary amine groups can the quaternary ammonium salt groups be generated on the surface of the polyamide through a chemical reaction with the sulfonyl chloride groups.

[0152] The water flux, MgCl2 desalination rate, LiCl desalination rate and magnesium-lithium separation factor of the composite membrane of the embodiment and the comparative example were tested, and the results are shown in Table 2.

[0153] Table 2

[0154]

[0155] It can be seen from Table 2 that the sulfonyl chloride group in the monomer containing the sulfonyl chloride group reacts with the tertiary amine group in the polyamide separation layer to convert the tertiary amine into a quaternary ammonium salt group with a positive charge. The repulsive effect between the positive charges improves the retention effect of the separation membrane for magnesium ions, thereby improving the magnesium-lithium separation efficiency.

[0156] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A positively charged composite membrane, characterized in that: The composite membrane comprises a bottom layer, a porous support layer and a polyamide separation layer arranged in sequence; Wherein, the polyamide separation layer contains a quaternary ammonium salt structure represented by Formula I and / or Formula II; Wherein, X is a halogen; Ar1 ​​and Ar2 are each independently a residue after the reaction of a monomer containing a sulfonyl chloride group.

2. The positively charged composite membrane according to claim 1, wherein X is Cl, Br or I; Preferably, the monomer containing a sulfonyl chloride group is selected from benzenesulfonyl chloride, o-toluenesulfonyl chloride, m-toluenesulfonyl chloride, p-toluenesulfonyl chloride, 2-ethylbenzenesulfonyl chloride, 3-ethylbenzenesulfonyl chloride, 4-ethylbenzenesulfonyl chloride, 2-chlorobenzenesulfonyl chloride, 3-chlorobenzenesulfonyl chloride, 4-chlorobenzenesulfonyl chloride, 2-fluorobenzenesulfonyl chloride, 3-fluorobenzenesulfonyl chloride, 4-fluorobenzenesulfonyl chloride, 2-nitrobenzenesulfonyl chloride, 3-nitrobenzenesulfonyl chloride, 4-nitrobenzenesulfonyl chloride, 2-bromobenzenesulfonyl chloride, 3-bromobenzenesulfonyl chloride, 4-bromobenzenesulfonyl chloride, Sulfonyl chloride, 2-iodobenzenesulfonyl chloride, 3-iodobenzenesulfonyl chloride, 4-iodobenzenesulfonyl chloride, 4-chloro-3-nitrobenzenesulfonyl chloride, 2-chloro-4-fluorobenzenesulfonyl chloride, p-dodecylbenzenesulfonyl chloride, p-butylbenzenesulfonyl chloride, 5-chloro-2-methylbenzenesulfonyl chloride, 3,5-dichlorobenzenesulfonyl chloride, 4-isopropoxybenzenesulfonyl chloride, 4-(trifluoromethoxy)benzenesulfonyl chloride, p-acetamidobenzenesulfonyl chloride, 2-cyanobenzenesulfonyl chloride, 3-cyanobenzenesulfonyl chloride, 4-cyanobenzenesulfonyl chloride, 2,4,6-trimethylbenzenesulfonyl chloride Sulfonyl chloride, 2,4,6-triisopropylbenzenesulfonyl chloride, 2,4,5-trichlorobenzenesulfonyl chloride, 2,5-dimethoxybenzenesulfonyl chloride, p-tert-butylbenzenesulfonyl chloride, 4-bromo-2-fluorobenzenesulfonyl chloride, 1-naphthalenesulfonyl chloride, 2-naphthalenesulfonyl chloride, 6-chloro-2-naphthalenesulfonyl chloride, 7-chloro-2-naphthalenesulfonyl chloride, 5-chloro-2-naphthalenesulfonyl chloride, 8-chloro-2-naphthalenesulfonyl chloride, 2-thiophenesulfonyl chloride, 2-chloropyridinesulfonyl chloride, 4,4'-oxybisbenzenesulfonyl chloride, 1,4-benzenedisulfonyl chloride, 1,3 At least one of -benzenedisulfonyl chloride, 4-amino-6-chloro-1,3-benzenedisulfonyl chloride, 1,2-benzenedisulfonyl chloride, 4,5-dichloro-1,3-benzenedisulfonyl chloride, 4,4'-biphenyledisulfonyl chloride, methylsulfonyl chloride, trichloromethylsulfonyl chloride, ethylsulfonyl chloride, 2-chloroethanesulfonyl chloride, propylsulfonyl chloride, butylsulfonyl chloride, 1,4-butanedisulfonyl chloride, 1,3-propanedisulfonyl chloride, 1,5-pentanedisulfonyl chloride, naphthalene-1,5-disulfonyl chloride and naphthalene-2,6-disulfonyl chloride.

3. The positively charged composite membrane according to claim 1 or 2, wherein: The content of nitrogen atoms in the quaternary ammonium salt structure in the positively charged composite film is 0.1-2 at.%, preferably 0.5-1.5 at.%; Preferably, the content of sulfur atoms in the positively charged composite film is 0.1-2 at.%, preferably 0.5-1.5 at.%.

4. The positively charged composite membrane according to any one of claims 1 to 3, wherein: The surface Zeta potential of the positively charged composite membrane is -10 mV to 5 mV, preferably -5 mV to 5 mV.

5. The positively charged composite membrane according to any one of claims 1 to 4, wherein: The average pore size of the positively charged composite membrane is 0.1-0.4 nm, preferably 0.15-0.3 nm.

6. The positively charged composite membrane according to any one of claims 1 to 5, wherein: The contact angle of the positively charged composite film is 40-70°, preferably 40-60°.

7. The positively charged composite membrane according to any one of claims 1 to 6, wherein: The thickness of the bottom layer is 30-150 μm, preferably 50-120 μm; Preferably, the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm; Preferably, the thickness of the polyamide separation layer is 10-500 nm, preferably 50-300 nm.

8. A method for preparing a positively charged composite membrane, characterized in that: The preparation method comprises the following steps: S1, preparing a porous supporting layer on the bottom layer; S2, the membrane layer obtained in step S1 is first contacted with an aqueous phase of a polyamine containing a tertiary amine group, and is second contacted with an organic phase containing a polyacyl chloride, and after heat treatment, a composite membrane containing a polyamide separation layer is obtained; S3, contacting the composite membrane with an organic solution of a monomer containing a sulfonyl chloride group, and drying to obtain the positively charged composite membrane.

9. The preparation method according to claim 8, wherein: In step S2, the polyamine containing a tertiary amine group is selected from at least one of polyethyleneimine, polyethylene polyamine, 1-aminopiperazine, 1,4-diaminopiperazine, 1,4-piperazine diethylamine and 1,4-bisaminopropylpiperazine; Preferably, the concentration of the polyamine containing tertiary amine groups in the aqueous phase of the polyamine containing tertiary amine groups is 0.1wt%-10wt%, preferably 0.5wt%-2.5wt%; Preferably, the polyacid chloride is selected from at least one of 1,3,5-benzene trimethylene dicarboxylic acid chloride, 1,2-phthaloyl dicarboxylic acid chloride, 1,3-phthaloyl dicarboxylic acid chloride, 1,4-phthaloyl dicarboxylic acid chloride and adipoyl dicarboxylic acid chloride; Preferably, the concentration of the polyacyl chloride in the organic phase containing the polyacyl chloride is 0.01wt%-1wt%, preferably 0.1wt%-0.5wt%; Preferably, the amount of the aqueous phase of the polyamine containing tertiary amine groups and the organic phase containing polyacid chlorides is such that the mass ratio of the polyamine containing tertiary amine groups to the polyacid chlorides is 0.1-10:1, preferably 0.5-5:1; Preferably, the first contact time is 5-100 s, preferably 10-60 s; Preferably, the second contact time is 10-200s, preferably 20-120s; Preferably, the heat treatment conditions include: heat treatment temperature of 40-150° C., preferably 50-120° C.; heat treatment time of 0.5-10 min, preferably 1-5 min.

10. The preparation method according to claim 8 or 9, wherein: In step S3, the monomer containing a sulfonyl chloride group is selected from benzenesulfonyl chloride, o-toluenesulfonyl chloride, m-toluenesulfonyl chloride, p-toluenesulfonyl chloride, 2-ethylbenzenesulfonyl chloride, 3-ethylbenzenesulfonyl chloride, 4-ethylbenzenesulfonyl chloride, 2-chlorobenzenesulfonyl chloride, 3-chlorobenzenesulfonyl chloride, 4-chlorobenzenesulfonyl chloride, 2-fluorobenzenesulfonyl chloride, 3-fluorobenzenesulfonyl chloride, 4-fluorobenzenesulfonyl chloride, 2-nitrobenzenesulfonyl chloride, 3-nitrobenzenesulfonyl chloride, 4-nitrobenzenesulfonyl chloride, 2-bromobenzenesulfonyl chloride, 3-bromobenzenesulfonyl chloride, 4- Bromobenzenesulfonyl chloride, 2-iodobenzenesulfonyl chloride, 3-iodobenzenesulfonyl chloride, 4-iodobenzenesulfonyl chloride, 4-chloro-3-nitrobenzenesulfonyl chloride, 2-chloro-4-fluorobenzenesulfonyl chloride, p-dodecylbenzenesulfonyl chloride, p-butylbenzenesulfonyl chloride, 5-chloro-2-methylbenzenesulfonyl chloride, 3,5-dichlorobenzenesulfonyl chloride, 4-isopropoxybenzenesulfonyl chloride, 4-(trifluoromethoxy)benzenesulfonyl chloride, p-acetamidobenzenesulfonyl chloride, 2-cyanobenzenesulfonyl chloride, 3-cyanobenzenesulfonyl chloride, 4-cyanobenzenesulfonyl chloride, 2,4,6-trimethylbenzenesulfonyl chloride Benzenesulfonyl chloride, 2,4,6-triisopropylbenzenesulfonyl chloride, 2,4,5-trichlorobenzenesulfonyl chloride, 2,5-dimethoxybenzenesulfonyl chloride, p-tert-butylbenzenesulfonyl chloride, 4-bromo-2-fluorobenzenesulfonyl chloride, 1-naphthalenesulfonyl chloride, 2-naphthalenesulfonyl chloride, 6-chloro-2-naphthalenesulfonyl chloride, 7-chloro-2-naphthalenesulfonyl chloride, 5-chloro-2-naphthalenesulfonyl chloride, 8-chloro-2-naphthalenesulfonyl chloride, 2-thiophenesulfonyl chloride, 2-chloropyridinesulfonyl chloride, 4,4'-oxybisbenzenesulfonyl chloride, 1,4-benzenedisulfonyl chloride, 1,3 At least one of -benzenedisulfonyl chloride, 4-amino-6-chloro-1,3-benzenedisulfonyl chloride, 1,2-benzenedisulfonyl chloride, 4,5-dichloro-1,3-benzenedisulfonyl chloride, 4,4'-biphenyledisulfonyl chloride, methylsulfonyl chloride, trichloromethylsulfonyl chloride, ethylsulfonyl chloride, 2-chloroethanesulfonyl chloride, propylsulfonyl chloride, butylsulfonyl chloride, 1,4-butanedisulfonyl chloride, 1,3-propanedisulfonyl chloride, 1,5-pentanedisulfonyl chloride, naphthalene-1,5-disulfonyl chloride and naphthalene-2,6-disulfonyl chloride.

11. The preparation method according to any one of claims 8 to 10, wherein: In step S3, in the organic solution, the concentration of the monomer containing the sulfonyl chloride group is 0.01wt%-5wt%, preferably 0.1wt%-2.5wt%; Preferably, the ratio of the volume of the organic solution to the membrane area of ​​the composite membrane is 0.05-1 mL / cm 2 ; Preferably, the contact conditions include: contact time is 10s-10min, preferably 1min-5min; Preferably, the drying conditions include: drying temperature of 30-80°C, preferably 40-60°C; drying time of 0.5-5 min, preferably 1-3 min.

12. A positively charged composite membrane prepared by the preparation method according to any one of claims 8 to 11.

13. Use of the positively charged composite membrane according to any one of claims 1 to 8 and 12 in the field of water treatment and separation.

Citation Information

Patent Citations

  • Polyamide nanofiltration membrane with pattern surface and preparation method

    CN112275140A

  • Acid-resistant composite nanofiltration membrane and preparation method thereof

    CN112642305A

  • Acid-resistant composite nanofiltration membrane and preparation method thereof

    CN113559728A

  • Acid-resistant composite membrane as well as preparation method and application thereof

    CN114432903A

  • Composite nanofiltration membrane as well as preparation method and application thereof

    CN116272438A